Toolkit for Programming Assistance to Orphans and Vulnerable Children (OVC) in Sub-Saharan Africa - Tovo, Maurizia; Prywes, Menahem; Kielland, Anne; Gibbons, Catherine; Saito, Junko (World Bank, Washington, DC, 2012)
Orphans and other vulnerable children (OVC) are among the most vulnerable population groups in Africa. Without support and protection, they are exposed to the risk of abusive labor, lack of education, malnutrition, disease, and death. Estimates indicate that 20 percent of children in Sub-Saharan Africa are OVC. They constitute such a large group that, to achieve the Millennium Development Goals (MDGs), OVC concerns need to be mainstreamed into relevant World Bank projects and programs. This brief note refers to the toolkit designed as a web-based product to make it a widely accessible, live document. It draws on a large array of experiences and material from international agencies and nongovernmental organizations (NGOs), hence helping to disseminate lessons - good and bad - learnt in a variety of settings. The Toolkit is organized in four parts and twenty-four sections.